Application of Luria Approach to Management of Autistic Spectrum Disorders - Markiewicz, K (KnE Life Sciences, 2018)
Autistic persons show considerable difficulties in the ability of self-control including attention, motor reactions, resistance to distractions and delay of gratification, which are presently labelled as executive functions. The present paper describes dynamics of developmental changes in executive functions of 25 autistic children, patients of Specialised Clinic of Diagnosis and Rehabilitation in Lublin, Poland, during their early and late childhood. In accordance with Luria original approach the assessment of disorders observed was closely connected with therapeutic procedure. It made possible getting deeper insight into the difficulties encountered by the children and refinement of the course of therapy at the same time. Significant progressive changes in the development of executive functions were observed in the examined children. A significant correlation among an ability to control one’s own reactions and cognitive functions, communication, and an ability to imitate others as well as general motor agility was stated. It allows the conclusion that autistic children are able to acquire an ability to change their former behaviours. They are, therefore, capable of understanding that a previous rule may be exchanged for the other, and they are also able to refrain from awaiting an immediate gratification. Keywords: Autism, executive functions, diagnosis, therapy, Luria approach